Deinstitutionalization of Status Offenders: a Study of Intervention Practices for Youth in Seven Cities in the United States, 1987-1991 - Klein, Malcolm ([Verlag nicht ermittelbar], 1994)
This data collection focuses on status offenders--those juveniles who commit acts (such as running away, habitual truancy, and possession of alcohol) that are forbidden to minors but not to adults. The purpose of this study was to connect legislative intent, service delivery systems, and youth responses in order to provide guidelines for future status offender legislation and practice. In the selection of sampling sites, three categories of intervention philosophy were represented: (1) deterrence, which recommends sanctions and control through the juvenile justice system, (2) treatment, which recommends emotional adjustment strategies through the community mental health system, and (3) normalization, which recommends little or no professional response. Respondents from youth service agencies in seven cities in the United States were asked about service delivery system characteristics (such as types of referral sources, how often they were used, and length of client service period), organizational characteristics (such as public versus private auspices, sources of funding, and educational level of staff), and youth characteristics (such as family situation, school status, and educational attainment of principal adults in the home). Demographic variables for status offenders included gender, race, age, and type of residence. Interviews with youths were also conducted and included a self-concept scale, by which youths could categorize themselves as delinquent, disturbed, and/or conforming. The units of analysis for this study are the individual and the youth service agency.